2004
DOI: 10.1097/01.ju.0000132564.27665.fb
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cholinergic Drugs on Ureteral Function in Anesthetized Dogs

Abstract: Our results demonstrate that in anesthetized dogs cholinergic receptor stimulation has a suppressive effect on ureteral pressure and peristalsis in obstructed ureters, in contrast to its activation of bladder smooth muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Carbachol also decreases ureteric pressure and peristalsis in partially or completely obstructed ureters of anaesthetised dogs in a manner unaffected by muscarinic antagonists (Tomiyama et al, 2004).…”
Section: Role Of Autonomic Nervous Supplymentioning
confidence: 98%
“…Carbachol also decreases ureteric pressure and peristalsis in partially or completely obstructed ureters of anaesthetised dogs in a manner unaffected by muscarinic antagonists (Tomiyama et al, 2004).…”
Section: Role Of Autonomic Nervous Supplymentioning
confidence: 98%
“…Studies to evaluate ureteral peristalsis have largely used endoluminal methods, employing either a pressure transducer [1][2][3][4] or an ultrasound probe 5 to evaluate ureteral physiology. However, these endoluminal devices can themselves alter ureteral peristalsis, and, hence, intraluminal evaluation technologies cannot be applied to measure ureteral peristalsis and the ureter's response to interventions such as stenting accurately.…”
Section: Introductionmentioning
confidence: 99%
“…However, Roshani et al [24] demonstrated that smooth muscle motor activity in the mid and the distal ureter was not modulated by muscarinic receptors in the porcine model. In another study, cholinergic receptor stimulation by muscarinic agonist carbachol in anesthetized dogs had a suppressive effect on ureteral pressure and peristalsis in obstructed ureters [25] . Tomiyama et al [26] suggested that carbachol-induced contraction in the isolated canine ureter was mediated through the M 3 -receptor.…”
Section: Muscarinic Acetylcholine Receptorsmentioning
confidence: 99%